Regionalisation and specialization of law firms in Singapore : the issues and possibilities for the future. - Lee, Chi Wi. (2009)
This dissertation examines the issues concerning regionalisation and specialisation of law firms - the role that Singapore law firms could play in keeping up with our Republic's economic expansion and providing the support and specialist skills that are needed by Singapore enterprises' regional activities.